THE EFFECT OF EMPOWERING LEADERSHIP AND OCB ON EMPLOYEE PERFORMANCE - Hasan, Muh; Ardianto, Ardianto; Muliati, Lisdewi; Nasution, Donni Alnis (Jurnal Comparative: Ekonomi dan Bisnis, 2024)
The purpose of this study is to find out how empowering leaderhsip and organizational citizenship behavior (OCB) influence the performance of Matahari Department Store  employees, Lippo Karawaci. The population of this research is 115 people, using purposive sampling method, the research sample is 87 people. The analytical method used is multiple regression analysis. The results of the study show that empowering leadership and OCB partially have a significant influence on the performance of Matahari Department Store Lippo Karawaci employees. Simultaneously empowering leadership and OCB have a significant influence on the employee performance of Matahari Department Store Lippo Karawaci. And the most dominant influence on employee performance is empowering leadership.